Analysis of Criminal Responsibility of Indirect Perpetrators in Corruption Crimes: A Literature Review of the Supreme Court Decision Number 2383 K/Pid.Sus/2023 - Mhd. Ilham Nasution; Muhammad Arif Sahlepi; Ismaidar Ismaidar (JURNAL HUKUM SEHASEN, 2026)
This study aims to analyze in-depth the criminal liability of indirect perpetrators in corruption crimes through a literature review of Supreme Court Decision Number 2383 K/Pid.Sus/2023. The phenomenon of corruption as an extraordinary crime often involves intellectual actors who are not directly involved in the physical losses of state finances, but control the crime through policies, official authority, or structured acts of omission. This study uses a normative juridical approach by examining laws and regulations related to criminal law doctrines regarding participation, as well as the judges' considerations in the decisions reviewed. The results of the analysis indicate that indirect perpetrators can be held criminally responsible if their role through policies, directives, or acts of omission clearly contributes to the occurrence of corruption crimes. The Supreme Court in this decision expanded the application of the doctrine of participation, which allows orderers and intermediaries to be subject to criminal sanctions even though they do not directly carry out physical actions. The element of fault (mens rea) for indirect perpetrators is proven through knowledge and intent regarding potential deviations arising from their instructions or authority. Causally, the established policy has been proven to be a determining factor in enabling the occurrence of the crime. This decision has significant implications for the effectiveness of the justice system in addressing structured corruption and provides a deterrent effect for structural authority holders. However, this broadening of interpretation also presents challenges to legal certainty and the risk of disparity in decisions due to the lack of standard guidelines in assessing the degree of involvement of indirect perpetrators. This study emphasizes the importance of developing clear and consistent legal guidelines and improving the capacity of judges to understand the doctrine of inclusion to maintain the principle of proportionality of punishment and legal certainty in Indonesia.